Mainstream care work films a new Filipino genre as an assertion of contemporary history - Bantugan, Brian Saludes (2014)
Access online through this link: https://www.plarideljournal.org/article/mainstream-care-work-films-a-new-filipino-genre-as-an-assertion-of-contemporary-history
Keywords: Film criticism; Filipino foreign workers; Film genres